2003
DOI: 10.2109/jcersj.111.81
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Boron Nitride Powder in Wet Oxygen.

Abstract: Oxidation kinetics of hexagonal boron nitride powder in 8÷ O 2 20÷ H 2 O/balance argon was investigated at 9001100 C. Paralinear weight change curves were observed. The rate constant of BN oxidation in 8÷ O 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…It was reported that oxidation of BN to B 2 O 3 (l) starts at about 1123 K and B 2 O 3 (l) further reacts with water vapor to form various H x B y O z (g) species . A number of studies have been performed on the oxidation behavior of BN and the oxidation reaction of BN proposed by Oda and Yoshio is generally accepted as following: BN(s)+34O2(g)=12B2O3(l)+12N2(g) In view of the recession of BN in water, Coffer and Economy examined a series of BN powder with different interplanar [d (002)] spacings between 0.333 and 0.367 nm in water vapor. The samples with larger interplanar spacings exhibited greater weight loss in a steam of H 2 O/air and H 2 O/N 2 at 973 K. Mass spectrometry indicated that the primary volatile product was HBO 2 with smaller amounts of H 3 BO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that oxidation of BN to B 2 O 3 (l) starts at about 1123 K and B 2 O 3 (l) further reacts with water vapor to form various H x B y O z (g) species . A number of studies have been performed on the oxidation behavior of BN and the oxidation reaction of BN proposed by Oda and Yoshio is generally accepted as following: BN(s)+34O2(g)=12B2O3(l)+12N2(g) In view of the recession of BN in water, Coffer and Economy examined a series of BN powder with different interplanar [d (002)] spacings between 0.333 and 0.367 nm in water vapor. The samples with larger interplanar spacings exhibited greater weight loss in a steam of H 2 O/air and H 2 O/N 2 at 973 K. Mass spectrometry indicated that the primary volatile product was HBO 2 with smaller amounts of H 3 BO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For high‐density CVD BN, the kinetics appeared to follow paralinear behavior. Oda et al . pointed out that the oxidation behavior of α‐BN powder followed paralinear rate law in 8 vol% O 2 –20 vol% H 2 O/balance argon between 1173 and 1373 K. It is important to understand the reaction behavior and the related mechanism of BN recession in water vapor to identify the specific fields and working temperature range of the application.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the expression of t ¤1 and t ¤2 [Eqs. (10) and (12)], the apparent activation energy ¦E d and ¦E r can be further extracted to be 105.8 and 93.5 kJ/mol.…”
Section: Application Of Rpp Modelmentioning
confidence: 99%
“…2),7)13) Oda et al 10) dealt with the oxidation kinetics of hexagonal BN powder in 8%O 2 20%H 2 O/balance argon at 11731373 K. Paralinear weight change curves were observed. A shrinking sphere model was adopted to treat the reaction of BN with the activation energy of 170 kJ/mol or so, indicating the interface reaction of BN and water vapor was the rate-controlling step.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is dicult to directly compare their results and our results, this degradation probably resulted from an increase in aw size by the preferential attack of water or agents in the inter granular phase. 10) …”
Section: Bending Strengthmentioning
confidence: 99%